2021
DOI: 10.1177/20587392211036825
|View full text |Cite
|
Sign up to set email alerts
|

Persistent lymphopenia after diagnosis of COVID-19 predicts acute respiratory distress syndrome: A retrospective cohort study

Abstract: Background Lymphopenia is a marker of immunosuppression after severe coronavirus disease-2019 (COVID-19) which is characterized by acute respiratory distress syndrome (ARDS). This study aimed to evaluate the relationships between persistent lymphopenia and ARDS. Methods A retrospective cohort study of 125 patients with COVID-19 admitted to government-designated treatment center between 14 January 2020, and 20 March 2020 was conducted. We recorded all complete blood cell counts during the day 0th, 3rd, and 7th … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 23 publications
0
6
1
Order By: Relevance
“…However that, some of laboratory findings The current study inconsistent with the findings of other comparative studies [13,19,20] in that lymphopenia was more common and cardinal laboratory finding in COVID-19 patients than in patients without the disease [37,39]. Although many studies have shown that a low lymphocyte count may predict the severity of the COVID-19 [40,41], in the current study low lymphocyte counts did not predict the disease status, and this may be because of co-morbidities that could be associated with an increased risk of lymphopenia, such as hypertension and diabetes [42] which are really common co-morbidities in this study. As a result, significant difference may not be observed among patients with and without COVID-19 as the comparability of marked systemic increase of inflammatory mediators and cytokines which contribute to comorbid and COVID-19-associated lymphopenia.…”
Section: Plos Onecontrasting
confidence: 98%
“…However that, some of laboratory findings The current study inconsistent with the findings of other comparative studies [13,19,20] in that lymphopenia was more common and cardinal laboratory finding in COVID-19 patients than in patients without the disease [37,39]. Although many studies have shown that a low lymphocyte count may predict the severity of the COVID-19 [40,41], in the current study low lymphocyte counts did not predict the disease status, and this may be because of co-morbidities that could be associated with an increased risk of lymphopenia, such as hypertension and diabetes [42] which are really common co-morbidities in this study. As a result, significant difference may not be observed among patients with and without COVID-19 as the comparability of marked systemic increase of inflammatory mediators and cytokines which contribute to comorbid and COVID-19-associated lymphopenia.…”
Section: Plos Onecontrasting
confidence: 98%
“…Meanwhile, the acquired immunosuppression was more severe, indicated by lower lymphocyte counts. 16 Moreover, the proportion of corticosteroid therapy and ECMO support in patients with COVID-19 was even higher, while the use of CRRT and invasive mechanical ventilation was lower, compared with CrKP patients. The hospitalized mortality, ICU and total length of hospital stay were also lower/shorter than that in patients with viral sepsis, and similar results were obtained after being adjusted for age, gender, and PaO 2 /FiO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Lymphopenia and the depletion of T lymphocyte subsets were found in 98% (153/157) of patients infected by SARS-CoV in 2003 without any preexisting hematological disorders [ 372 ]. Correspondingly, patients infected by SARS-CoV-2 are associated with persistent lymphopenia [ 373 , 374 ] and functional exhaustion of lymphocytes [ 375 ]. COVID-19 disease progression is correlated with a nearly three-fold increased risk of severe COVID-19 (random effects model, OR = 2.99, 95% CI: 1.31–6.82) [ 376 ], while low lymphocyte counts in patients are deemed to be effective predictors of disease severity and hospitalization [ 377 , 378 ].…”
Section: Melatonin Protects Mitochondria and Atp Production To Inhibi...mentioning
confidence: 99%